Development and Initial Characterisation of a Localised Elastin Degradation Ex Vivo Porcine Aortic Aneurysm Model - Matthew Laffey; Brooke Tornifoglio; Caitríona Lally (Applied Sciences, 2023)
Aortic aneurysms (AA) occur in 4.8% of people causing 150,000 deaths annually. While endovascular aneurysm repairs reduce surgical morbidity, device-related failures (leak/displacement) are frequent highlighting the need for test models that better represent the mural geometry and compliance changes in human AAs. We aimed to develop and characterise an ex vivo porcine aortic model of AA. The optimal duration of tissue elastase exposure to emulate AA changes in elastin microstructure and content was determined using porcine aortic rings. Elastase-induced changes were quantified morphologically, and mechanical properties assessed via ring tensile testing. Subsequent experiments tested the potential for localised elastase treatment in a 1 cm segment of porcine aorta using a specially designed 3D printed rig. The effect on pressure-diameter behaviour was investigated via inflation-extension testing. Elastase treatment produced time dependent decreases in elastin, resulting in an increased tensile modulus and circumferential length in the ring samples in the final phase of the J-shaped tissue stress-strain curves. In whole aortic segments, localised elastase-induced luminal degradation was successfully limited to a central region. The degree of elastin degradation achieved was sufficient to cause localised dilation with respect to controls under physiological pressures. Localised elastin degradation in porcine aortic segments is feasible and emulates the changes seen clinically in aortic aneurysms.